Analysis of the Effectiveness of a Technological Solution to Simultaneously Mitigate Soil Degradation and Control the Infestation of Invasive Plants - Tsuchiya, Lucas Hubacek; Silva, Alexandre Marco da (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Geotextile-based products have been considered as an adequate alternative to mitigate soil degradation processes, either by erosion or invasion by weeds. Thus, we assessed the efficiency of a bag confectioned with jute fabric and filled with mowed grass. We constructed six experimental plots considering two experimental conditions - three with the control (uncovered) and three covered with the product we generated (jute bag). We conducted the study during a rainy period and analyzed the efficiency of the product using the indicators: soil-chemical balance (including organic matter), soil-water repellence (hydrophobicity), changes in the microtopography of the plots, and emergence and growth of plants.
Keywords: biodegradable material-based geotextile; jute fiber; soil reinforcement; leaching; vegetation growth control